2020
DOI: 10.3389/fonc.2020.00797
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Pre-Treatment Prognostic Nutritional Index in Esophageal Cancer: A Systematic Review and Meta-Analysis

Abstract: Background: Prognostic nutritional index (PNI), combining albumin and lymphocyte counts, which represent the nutritional and immune status, was considered as an effective predictor for the patient's prognosis after surgery. To comprehensively analyze the relative effectiveness of prognostic performance of pretreatment PNI in esophageal cancer (EC), we performed this meta-analysis.Methods: We performed a systematic search in PubMed, Embase, CNKI, and Web of Science. The hazard ratios (HRs) or odds ratios (ORs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…The mechanism by which a low nutritional status decreases the survival time of breast cancer patients is still not sufficiently understood. The PNI, as a systemic immune–nutrition index based on the peripheral lymphocyte count and serum albumin levels, represents the immune and nutritional status and is also a significant biomarker for many tumors ( Dai et al, 2020 ; Hao et al, 2020 ; Zhang et al, 2020 ). The PNI was initially developed to evaluate the postoperative complications in patients who received gastrointestinal surgery ( Onodera et al, 1984 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which a low nutritional status decreases the survival time of breast cancer patients is still not sufficiently understood. The PNI, as a systemic immune–nutrition index based on the peripheral lymphocyte count and serum albumin levels, represents the immune and nutritional status and is also a significant biomarker for many tumors ( Dai et al, 2020 ; Hao et al, 2020 ; Zhang et al, 2020 ). The PNI was initially developed to evaluate the postoperative complications in patients who received gastrointestinal surgery ( Onodera et al, 1984 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that low PNI was correlated with male sex (19,20), old age (19), positive lymph node status (20), advanced T stage (19,20), and body mass index (BMI) (20), but not metastasis (19) or the differentiation grade (19,20) of EC. Meanwhile, another study found that patients with low PNI were at high risk of postoperative complications (21). In a subgroup analysis, the pooled HR was found to be statistically significant across different groups (e.g., country, year of publication, sample size, cutoff value, and quality scores) (19,20).…”
Section: Esophageal Cancer (Ec)mentioning
confidence: 94%
“…Three systematic reviews and meta-analyses have examined the prognostic value of PNI in EC, irrespective of histological type and treatment (19)(20)(21). Most of the included studies were identical, and thus the findings are similar.…”
Section: Esophageal Cancer (Ec)mentioning
confidence: 97%
“…PNI reflects the nutritional and immunologic status of patients with cancer and is a prognostic factor in several solid tumors ( 9 ). Low PNI is associated with poor prognosis in some cancers, such as pancreatic ( 10 ), lung ( 11 ), esophageal cancer (EC) ( 12 ), and ovarian ( 13 ) cancers, and nasopharyngeal carcinoma ( 14 ). Many studies have also explored the prognostic significance of PNI in patients with RCC; however, the results have been inconsistent ( 15 24 ).…”
Section: Introductionmentioning
confidence: 99%